Relative age effect reversal on the junior-to-senior transition in world-class athletics - Brustio, P. R.; Stival, M.; Boccia, G. (Journal of Sports Sciences, 2023)
The relative age effect (RAE) is a selection bias resulting from the interaction between the selected dates and birthdates. Nevertheless, the impact of birthdate on the junior-to-senior transition in international track and field is unclear. This study aimed to quantify the RAE`s magnitude and test if birthdate affects the junior-to-senior transition rate. The birthdate and performances of 5,766 sprinters (female: 51.0%) and 5,863 jumpers (female: 45.9%) were collected. Elite athletes (operationally defined as the World`s all-time Top 200, 100 and 50 athletes) were identified according to Under 18 and Senior categories. Skewed quartile distributions were observed in the Under 18 (effect size ranged = 0.15-0.10) but not in the Senior category. RAE magnitude increased according to performance level (i.e., from Top 200 to Top 50) and was higher in males than females. Relatively younger athletes showed significantly higher transition rates with a higher chance of maintaining top level in the senior category (odds ratio (OR) ~ 1.64). The probability of maintaining success was lower for sprinters than jumpers (OR ~ 0.70), influenced by decade of birth and continental place but similar for male and female athletes. Data corroborate that relatively younger athletes are disadvantaged in the junior category but advantaged when transitioning to the senior category.